2018
DOI: 10.1038/s41467-018-03752-5
|View full text |Cite
|
Sign up to set email alerts
|

Rolling up transition metal dichalcogenide nanoscrolls via one drop of ethanol

Abstract: Two-dimensional transition metal dichalcogenides (TMDs) have attracted lots of interest because of their potential for electronic and optoelectronic applications. Atomically thin TMD flakes were believed capable to scroll into nanoscrolls (NSs) with distinct properties. However, limited by mechanical strength and chemical stability, production of high-quality TMD NSs remains challenging. Here, we scroll chemical vapor deposition-grown monolayer TMD flakes into high-quality NSs in situ in 5 s with a nearly 100%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
222
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(231 citation statements)
references
References 37 publications
9
222
0
Order By: Relevance
“…These narrow lines were recorded in the spectral range of ≈50 meV; thus, a large‐scale set of relatively uniform single‐photon emitters can be formed using such approach. Another interesting example is nanoscrolls produced by rolling up a MoS 2 monolayer within a drop of ethanol . The direct exciton emission from such nanoscrolls was registered with excitation by a 532‐nm laser line.…”
Section: Basic Optical Properties Of Tmd Nanotubes and Related Curvedmentioning
confidence: 99%
See 1 more Smart Citation
“…These narrow lines were recorded in the spectral range of ≈50 meV; thus, a large‐scale set of relatively uniform single‐photon emitters can be formed using such approach. Another interesting example is nanoscrolls produced by rolling up a MoS 2 monolayer within a drop of ethanol . The direct exciton emission from such nanoscrolls was registered with excitation by a 532‐nm laser line.…”
Section: Basic Optical Properties Of Tmd Nanotubes and Related Curvedmentioning
confidence: 99%
“…For other vdW tubular structures, the situation was different. For instance, the emission was observed from HfS 2 NTs, boron nitride NTs, and also from the nanoscrolls fabricated by rolling up the MoS 2 and WS 2 monolayers. On the contrary, the studies of chemically synthesized MoS 2 and WS 2 NTs were focused on such characteristics of tubes ensembles as absorption and optical limiting, that is, nonlinear saturation of light transmittance at high incident intensities .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these nanoscrolls not only hold the 2D characteristics, but also possess some new properties, just like the gapless and topological structure at the ends and interlayer galleries of graphene nanoscrolls . Similarly, nanoscrolls based on another type of representative 2D material,transition‐metal dichalcogenides (TMDCs) with a wider bandgap, show higher mobility with larger current density and better environmental stability than the monolayer triangle sheets . Benefiting from these features, MoS 2 and WS 2 nanoscrolls have improved photosensitivity than the 2D counterparts, presenting potential in the optoelectronic application.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Patra et al predicted that water nanodroplets could also guide the folding and rolling of planar graphene sheets, where the scrolling results from the interaction between capillarity and elasticity, and this prediction was then experimentally confirmed . More recently, Cui et al reported the rolling of transition metal dichalcogenides (TMDs) with the assistance of aqueous solutions such as ethanol. The fabricated nanoscrolls demonstrated obvious photoluminescence and stability in different atmospheres.…”
Section: Release Methodsmentioning
confidence: 99%
“…c) Schematic of rolling TMD monolayer flakes and TEM images of MoS 2 nanoscrolls (scale bars: 20 nm; inset = 2 nm). Adapted with permission . Copyright 2018, Springer Nature.…”
Section: Release Methodsmentioning
confidence: 99%